Sustainability and Consumer Behaviour - Kasim, Azilah (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book highlights the latest research findings on sustainability within the context of consumer behaviour. It brings together the collaborative work of researchers from Finland, Denmark, USA, the Netherland, Mexico, Korea, Saudi Arabia, Malaysia, Indonesia, Thailand, Taiwan and China to improve our understanding on consumer behaviour and its relationship with sustainable resource consumption. The thirteen chapters in this book focus on different aspects of consumer behaviour and sustainability, including purchase intentions towards recycled products, environment fit hospitality experiences, purchase intentions of recycling items, consumer loyalty, electric vehicle market consumption, consumption of the educational products, revisit intention, online complaint behaviour, consumer and CSR, eco-friendly behaviour, brand trust and social media consumer communication.